How do Female Teachers with Double Responsibilities Develop Grit in Self-Directed Professional Development in the CALL Context? - I Putu Indra Kusuma; Luh Putu Artini; Amelia Kartikawati (Universitas Sulawesi Barat, 2025)
This study aimed to explore how female English as a foreign language (EFL) teachers with double responsibilities as a wife/mother and teacher describe their grit in self-directed Professional Development (PD) in Computer-Assisted Language Learning (CALL) context and the challenges they face. This study employed a narrative inquiry approach to understand participants’ stories. The study recruited three female EFL teachers in Indonesia as the research participants. In Indonesia, a female teacher typically had double responsibilities by being a wife/mother in their family and a teacher in school. The first stage allowed the researcher to collect all data of biographical survey, teachers’ concept map, and narrative interview. Following the steps for qualitative content analysis, all the data were then being processed. In the second stage, the researcher provided these ideas value by combining or recreating them in a narrative way through stories. It was based on the idea that humans gave the world as well as their knowledge, action, and value through narrative constructions. The results showed: 1) Indonesian female EFL teachers’ grit in CALL context was typically described by their passion for teaching, support system (family, colleagues, students), and responsibility of being a teacher, and (2) during their journey of self-directed PD in the CALL context, female EFL teachers faced challenges in constructing grit such as time management, burnout, and stereotypes as novice teachers. The results were expected to provide a new perspective for schools and government in comprehending female EFL teachers’ needs and challenges.